Poczucie narodowe i nacjonalizm - Kmieciński, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
The present paper discusses the notion of "the sense of the nation" and "nationalism". Within ages various tendencies and interpretations were connected to these notions and those who spent their life time in indiscriminate language area and especially those who dit not experience the concern for mother tonque or the existence of their country were not always conscious of their significance. The article was limited to development of only some problems, as it seems, of significant meaning not concerned to the archaeological field. From the very vast number of problems these facts and experiences which are well-known or can be easily checked were chosen here while those which are doubtful or are only assumptions should be treated accordingly. Since nationalism is still the desease of our times it seems to be extremely important to explain the difference between the sense of the nation as a significant spiritual value and nationalism as moral wickedness.